Extrapleural Pneumonectomy for Sarcoma of the Lung in a Pediatric Patient - Schweigert, Michael; Almeida, Ana B.; Pablik, Jessica (The Thoracic and Cardiovascular Surgeon Reports, 2022)
Pediatric sarcomas are rare entities. Bone sarcomas and rhabdomyosarcoma are most common, whereas primary sarcoma of the lung is extremely uncommon. Pneumonectomy is only very infrequently performed in the pediatric population. We report on a 16-year-old girl with an undifferentiated high-grade pleomorphic sarcoma of the left lung. There was no comorbidity and no history of previous malignant disease. The huge tumor originated from the left lower lobe and had spread to the left pleura. As part of a multimodal approach, she underwent extrapleural pneumonectomy with en bloc resection of the pleura, lung, pericardium, and diaphragm.
Keywords: pediatric sarcoma; pediatric thoracic surgery; extrapleural pneumonectomy